Evaluation of post‐thaw CFU‐GM: clinical utility and role in quality assessment of umbilical cord blood in patients receiving single unit transplant. Issue 1 (22nd November 2019) - Hussein, Eiman; DeFor, Todd; Wagner, John E.; Sumstad, Darin; Brunstein, Claudio G.; McKenna, David H.
Abstract : BACKGROUND: The CFU assay is considered the only in vitro assay that assesses the biologic function of hematopoietic stem and progenitor cells (HSPC). STUDY DESIGN AND METHODS: To investigate the impact of post‐thaw CFU‐GM counts on the quality of umbilical cord blood (UCB), we studied transplant outcomes in 269 patients receiving single UCB transplant. We also correlated the post‐thaw CFU‐GM counts of 1912 units with the pre‐freeze and post‐thaw graft characteristics, hoping to optimize selection criteria of UCB. Data analysis included: total nucleated cells, viability, CD34+, nucleated red blood cells (NRBC), hematocrit, frozen storage time, and cord blood bank (CBB). RESULTS: We demonstrated an association between post‐thaw CFU‐GM dose and the speed of neutrophil and platelet engraftment (p < 0.01). Higher post‐thaw CFU‐GM dose showed an increased benefit for neutrophil and platelet engraftment (p < 0.01). Post‐thaw CD34+ cell dose and CFU‐GM dose were strongly correlated (r = 0.78). However, CFU‐GM dose showed additional benefit for patients receiving the lowest quartile of CD34+ dose. HLA disparity did not adversely impact either neutrophil or platelet engraftment. Post‐thaw CFU‐GM/million nucleated cells plated showed moderate correlation with pre‐freeze and post‐thaw CD34+ and weak correlation with other parameters. Post‐thaw CFU‐GM was not influenced by storage time, but was impacted by the CBB from which the unit is obtained (p < 0.01). CONCLUSION: Post‐thaw CFU‐GM is an effective measure of the quality and efficacy of the UCB graft, particularly adding valuable clinical information when the CD34+ cell dose is low. Consideration of pre‐freeze CD34+ cell content and CBB as additional selection criteria is warranted.